2020
DOI: 10.1016/j.jaccas.2020.06.033
|View full text |Cite
|
Sign up to set email alerts
|

A Case of an Aortic Dissection After Mechanical Chest Compression by LUCAS

Abstract: A 68-year-old man presented following a cardiac arrest. Cardiopulmonary resuscitation was performed by the Lund University Cardiopulmonary Assist System (LUCAS), a mechanical chest compression device. Investigations revealed an aortic dissection, which was likely an iatrogenic injury from mechanical cardiopulmonary resuscitation by LUCAS. This case highlights this potential complication. ( Level of Difficulty: Beginner. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Unresponsiveness to initial therapy of cardiogenic pulmonary edema implies that TAD developed spontaneously and not as a traumatic consequence of cardiopulmonary resuscitation. Nevertheless, chest compression-related aortic injuries should be taken into consideration in cardiac arrest survivors, especially after prolonged mechanical resuscitation and extracorporeal cardiopulmonary resuscitation, which are increasingly used [ 7 ]. To the best of our knowledge, cardiopulmonary resuscitation-induced TAD with an entry localized in the area of TAVR prosthesis has not been described in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…Unresponsiveness to initial therapy of cardiogenic pulmonary edema implies that TAD developed spontaneously and not as a traumatic consequence of cardiopulmonary resuscitation. Nevertheless, chest compression-related aortic injuries should be taken into consideration in cardiac arrest survivors, especially after prolonged mechanical resuscitation and extracorporeal cardiopulmonary resuscitation, which are increasingly used [ 7 ]. To the best of our knowledge, cardiopulmonary resuscitation-induced TAD with an entry localized in the area of TAVR prosthesis has not been described in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…Penov et al, 2022, reported the incidence of aortic rupture due to prolonged mechanical CPR with concomitant Impella, which means that even some fatal complications of CPR might be possible [8]. Ho et al, 2022, presented a case of aortic dissection that was most likely an iatrogenic injury due to mechanical cardiopulmonary resuscitation carried out using the Lund University Cardiopulmonary Assist System (LUCAS) [9].…”
Section: Introductionmentioning
confidence: 99%